The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages This pamphlet has been prepared by the Social Services Group of the Socialist Medical Association. All workers in the social services are invited to communicate with the Secretary, S.M.A., 59, New Oxford Street, London, W.C.1, for particulars of the Association and of the work of the Social Services Group. 15X/2/464/1